Hiss & tell [large type] - Brown, Rita Mae; Brown, Sneaky Pie, 1982- (Brown, Rita Mae. Mrs. Murphy mystery, 2023)
"Christmas is coming, but Harry's friend on the police force, Cynthia Cooper, warns that the season can bring an uptick in crime. Her words prove tragically prescient when Harry and her best friend Susan discover the body of a man by the side of the road. One suspicious death is bad enough, but when Cooper reports that two more bodies have been found, Harry knows trouble is afoot. The autopsies for all three bodies reveal the presence of a deadly drug. With help from her feline sidekicks, Mrs. Murphy and Pewter, Harry vows to find the answers and stop the spate of deaths so that all of Crozet can have a very merry Christmas"--